Annual Parole Survey, 1994 ([Verlag nicht ermittelbar], 2012)
The 1994 Annual Parole Survey provides a count of the total number of persons supervised in the community on January 1 and December 31, 1994, and a count of the number entering and leaving supervision during the year. The survey also provides counts of the number of parolees by certain characteristics, such as gender, race, Hispanic or Latino origin, and supervision status. This survey covers all 50 states, the District of Columbia, and the federal system.